2008
DOI: 10.1124/dmd.108.020370
|View full text |Cite
|
Sign up to set email alerts
|

Bioactivation of Flutamide Metabolites by Human Liver Microsomes

Abstract: ABSTRACT:Flutamide, a widely used nonsteroidal antiandrogen drug for the treatment of prostate cancer, has been associated with rare incidences of hepatotoxicity in patients. It is believed that bioactivation of flutamide and subsequent covalent binding to cellular proteins is responsible for its toxicity. A novel N-S glutathione adduct has been identified in a previous bioactivation study of flutamide (Kang et al., 2007). Due to the extensive first pass metabolism, flutamide metabolites such as 2-hydroxyfluta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
40
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(49 citation statements)
references
References 31 publications
(38 reference statements)
9
40
0
Order By: Relevance
“…10). It has been reported that two GSH adducts were detected in human liver microsomal incubation of FLU-1 in the presence of NADPH and GSH (Kang et al, 2008). These results suggest the protective role of hepatic GSH in flutamideinduced liver injury.…”
Section: Figsupporting
confidence: 59%
“…10). It has been reported that two GSH adducts were detected in human liver microsomal incubation of FLU-1 in the presence of NADPH and GSH (Kang et al, 2008). These results suggest the protective role of hepatic GSH in flutamideinduced liver injury.…”
Section: Figsupporting
confidence: 59%
“…It was identified as 2-methyl-N-[4-amino-3-(trifloromethyl)phenyl]propanamide (3) by correlation spectra together with published data. 6,8) Compound 4 (14 mg, 3.0%) was isolated as an off-white solid with a molecular formula C 9 H 9 F 3 N 2 O. The 1 H-NMR data of 4 differed from those of 3 in the absence of signals due to the isopropyl group and the presence of a methyl group instead.…”
Section: Resultsmentioning
confidence: 99%
“…3) In addition to 2-hydroxyflutamide mono-, di-and trihydroxylated flutamides have been identified. 8) The absence of the hydroxylated metabolites and the predominant presence of FLU-1 along with FLU-4 and FLU-6 in culture media suggest that the fungal metabolism of flutamide takes place exclusively via amide bond cleavage pathway (Chart 1). 3) Flutamide and its major microbial transformation product, FLU-1 are nitroaromatic compounds which undergo nitroreductive metabolism to yield FLU-6 and FLU-4 (detected in human urine).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations